The Comparative Literature Analysis of Collins' Novel 'The Hunger Games' and Veronica Roth's Novel 'Divergent' - Amirrudin Amirrudin; Ahmad Mustolih; Charimah Marta Ningrum (English Language Education Study Program of STKIP PGRI Banjarmasin, 2022)
The title of this research is The Comparative Literature Analysis in Suzanne Collins' Novel 'The Hunger Games' and Veronica Roth's Novel 'Divergent'. It compares the two main characters in each novel, Katniss and Tris, using a feminist approach. The purpose of the research is to reveal and to compare the feminist values conducted by the main characters and to examine the similarities and differences in the main character's role in influencing the novel's social conditions in terms of feminism. This study uses descriptive qualitative research. The data source comes from the novels The Hunger Games and Divergent. Based on the writer's analysis, it shows that Katniss and Tris have tough and dominant characters. Both of them also show the activities that engage with the feminist movement. Furthermore, Katniss and Tris are fighting injustice in their social environments, albeit in different ways. Katniss makes soft gestures while Tris does the confrontation.